Status Hukum Pulau-Pulau Terluar Indonesia - Oegroseno, Arif Havas (UI Scholars Hub, 2009)
Outer islands play important role to determine national boundaries. Legal status of ninety-two outer islands in Indonesia creates the basic law for Indonesia to be acknowledged as the Archipelagic State. Since the decision from International Court of Justice which won Malaysia over the Sipadan and Ligitan case on the basis of effective occupation, Indonesian people are having highly concerned on effective occupation. Effective occupation is an international law doctrine which arises from law of ancient Rome. Effective occupation is an administrative act without physical occupation. It can be applied to terra nullius territory. This paper discusses over the effective occupation in the case of Sipadan and Ligitan and the role of outer islands in the maritime diplomacy.